Quantitative proteomic analysis and verification identify global protein profiling dynamics in pig during the estrous cycle - Xin, Haiyun; Li, Baohong; Meng, Fanming; Hu, Bin; Wang, Sutian; Wang, Ying; Li, Jianhao (Frontiers in Veterinary Science, 2023)
The current estrus detection method is generally time-consuming and has low accuracy. As such, a deeper understanding of the physiological processes during the estrous cycle accelerates the development of estrus detection efficiency and accuracy. This study used label-free acquisition mass spectrometry to explore salivary proteome profiles during the estrous cycle (day −3, day 0, day 3, and day 8) in pigs. A total of 1155 proteins were identified in the label-free analysis, of which 115 were identified as differentially expressed proteins (DEPs) among different groups (P ≤ 0.05). Functional annotation revealed that the DEPs were clustered in calcium ion binding, actin cytoskeleton, and lyase activity. Parallel reaction monitoring (PRM) was applied to verify the relative profiles of protein expression, in which PHB domain-containing protein, growth factor receptor-bound protein 2, elongation factor Tu, carboxypeptidase D, carbonic anhydrase, and trefoil factor 3 were confirmed to be consistent in both label-free and PRM approaches. Comparative proteomic assays on saliva would increase our knowledge of the estrous cycle in sows and provide potential methods for estrus detection.